Strengthening NGO capability for advocacy an assessment - Alfiler, Ma. Concepcion P. (2001)
The Philippines recognized the emergence of nongovernmet organizations (NGOs) during their involvement in the First People Power and acknowledged them as state's partner in the 1987 Constitutition. At present, NGOs provide social services to marginalized and disadvantaged groups and help the disempowered members of the society to exercise their rights and participate in decisions benefitting them. The author elucidates that NGOs will always have a cause to fight for and this makes advocacy one of its key concerns. NGOs must have some preparation to grow as an organization that could bring changes and redistribution of power within society. They need professionals for this unique preparation.
Keywords: Balay Mindanaw Foundation, Inc; Civil society organizations; Community Action for Rural Development (CARD); Fellowship For Organizing Endeavors, Inc. (FORGE); Non-government organizations; Policy analysis